2012
DOI: 10.1097/ta.0b013e31823dc230
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized periosteal transfer from the medial femoral condyle

Abstract: Although not statistically significant because of the small sample size, our study might support the idea that both periosteal and corticoperiosteal flaps from the medial femoral condyle are effective, when associated with a bone graft, in the treatment of recalcitrant nonunions with small gaps. A further analysis of the results suggests, albeit no statistical significant, that structural and nonstructural bone grafts are both effective when associated with a vascularized periosteal or corticoperiosteal transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The comparative series by Hamada et al () observed a 100% union rate at a mean of 1.9 months with MFC treatment, opposed to 75% union at 5.5 months following NVBG. Vegas et al () concluded that time to union was similar between the three periosteal‐only flaps and five corticoperiosteal flaps.…”
Section: Resultsmentioning
confidence: 99%
“…The comparative series by Hamada et al () observed a 100% union rate at a mean of 1.9 months with MFC treatment, opposed to 75% union at 5.5 months following NVBG. Vegas et al () concluded that time to union was similar between the three periosteal‐only flaps and five corticoperiosteal flaps.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, flaps of periosteal autografts have been frequently used for the repair of articular cartilage [16]. In the management of recalcitrant nonunions with small gaps, both periosteal and corticoperiosteal flaps play a central role [17]. To bridge segmental bone defects Li et al implanted Cbfa-1 gene-modified tissue-engineered bone and vascularized periosteum.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical prospective study, Vegas et al showed that periosteum only and corticoperiosteal microvascular transfers from the medial femoral condyle were both effective on the acceleration of bone healing [17]. Periosteal cells are reported to be a major source of soft callus in bone fractures [6].…”
Section: Discussionmentioning
confidence: 99%